The Good, Bad and Ugly Sides of Internet Usage in the Workplace - Siew Ching J-Ho; T. Ramayah (Journal of Business and Social Review in Emerging Economies, 2016)
Objective: Computer was designed to help in human daily activities especially in replacing typewriter, a common tool in most offices. The purpose of this paper is to identify positive and negative effect of Internet usage, as well as its factors and impacts. Methodology: Reviews of articles are retrieved from databases of SCOPUS and Science Direct from 2006 to 2016. Results: Many people misuse the Internet for personal usage especially during working hours and it known as cyberloafing. Implication: Computer is used together with internet in the world of information technology for faster communication after 2000s. Internet and social media can improve work performance especially in marketing and communication. However, the misuse of internet had caused cyberloafing issues due to ease of access. Mostly, it is related to factors such as personality-related factors, organizational-related factors, and work-related factors.